2019
DOI: 10.34209/.v21i2.643
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Skeptisisme Profesional Auditor, Kompetensi, Independensi Dan Kompleksitas Audit Terhadap Kualitas Audit

Abstract: This study was conducted with the aim to examine the influence of The Auditor’s Professional Skepticism, Competence, Independence and Complexity of The Audit on Audit Quality. The sample used in this study is 70 auditor by using purposive sampling method. The analysis technique that used in this study is multiple linear regression with significance level of 5%. The results of this study indicate that the value of Adjusted R Square is 0.547 or 54,7% which means that the ability ofindependent variables namely th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 1 publication
3
10
0
10
Order By: Relevance
“…This study's results align with previous research conducted by Kusumawati and Syamsuddin (2018) also Nugrahaeni et al (2019), which state that professional skepticism has a significant direct effect on audit quality. Research by Popova (2013), Hussin et al (2017), andBeasley et al (2001), reveal that there is a significant relationship between professional skepticism and the detection of fraud also material misstatement which is a form of audit quality.…”
Section: Hypothesis Testingsupporting
confidence: 90%
See 2 more Smart Citations
“…This study's results align with previous research conducted by Kusumawati and Syamsuddin (2018) also Nugrahaeni et al (2019), which state that professional skepticism has a significant direct effect on audit quality. Research by Popova (2013), Hussin et al (2017), andBeasley et al (2001), reveal that there is a significant relationship between professional skepticism and the detection of fraud also material misstatement which is a form of audit quality.…”
Section: Hypothesis Testingsupporting
confidence: 90%
“…Some previous studies revealed a positive correlation between auditors' professional skepticism and audit quality. Kusumawati and Syamsuddin (2018) also Nugrahaeni et al (2019) state that professional skepticism directly affects audit quality, where an appropriate measure of audit quality lies in the auditor's conduct when conducting audits, one of which is professional skepticism. The research conducted by Popova (2013) and Beasley et al (2001) show that an attitude of skepticism will increase sensitivity in detecting fraud during the evaluation of evidence.…”
Section: Framework and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Competence is individual behavior that comes from the auditor, which has components to provide quality audit results. With audit quality, the information users can be fulfilled, and there is no error between the principal and the agent (Nugrahaen et al, 2019). The relationship between competence and audit quality is that the experience and knowledge possessed by the auditors in examining fraud will result in increased audit quality.…”
Section: H1: Competence Affects Professional Skepticismmentioning
confidence: 99%
“…Then independence also has a relationship with audit quality because auditors who apply an attitude of not being easily influenced and impartial to anyone can provide an opinion by audit evidence to improve the quality of the results of the examination that have been produced. Researchers have studied competence and independence related to audit quality (Maulana, 2015;Nugrahaen et al, 2019;Octavia & Widodo, 2015).…”
Section: Introductionmentioning
confidence: 99%